2019
DOI: 10.1136/bmjopen-2019-030905
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative exposure to ionising radiation from diagnostic imaging tests: a 12-year follow-up population-based analysis in Spain

Abstract: ObjectivesTo calculate each patient’s cumulative radiation exposure and the recurrent tests during a 12-year study period, according to sex and age, in routine practice.DesignRetrospective cohort study.SettingA general hospital with a catchment population of 224 751 people, in the Southeast of Spain.ParticipantsPopulation belonged to the catchment area of that hospital in 2007. We collected all consecutive diagnostic imaging tests undergone by this population until 31 December 2018. We excluded: imaging tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Also, a recent study by Rehani and Hauptman 18 demonstrated up to a sixfold variation between countries in the estimated number of patients receiving high cumulative effective doses relative to the population of a country. Two population-based studies 14 15 used well-defined and large study populations living in specific areas of Spain (224 751 people) 14 and the USA (54 447 adults). 15 They reported analyses of the subgroups of inhabitants undergoing at least one CT examination in the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a recent study by Rehani and Hauptman 18 demonstrated up to a sixfold variation between countries in the estimated number of patients receiving high cumulative effective doses relative to the population of a country. Two population-based studies 14 15 used well-defined and large study populations living in specific areas of Spain (224 751 people) 14 and the USA (54 447 adults). 15 They reported analyses of the subgroups of inhabitants undergoing at least one CT examination in the study period.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, all studies reported consistent and dramatic declines in all radiology examinations, with significant reductions in outpatient accesses of up to 70%, while examining the various imaging techniques showed reductions of 56% for MR, 53% for conventional radiology, and 47% for CT [15][16]; in particular for outpatients, the most significant decreases peaked for mammography examinations (94%), followed in descending order by nuclear medicine (85%), MRI (74%), ultrasound (64%), interventional radiology (56%), CT (46%), and radiography (22%) (17)(18) One study tracked the trend in wRWUs documenting an average decline of 52% in the United States during the pandemic peak. By modality, CT and traditional radiography (including mammography) together accounted for well over half of the total practice wRVU decreases (19).…”
Section: Discussionmentioning
confidence: 99%
“…For collecting data on imaging test frequency, we carried out procedures similar to those used in a previous study [ 29 ]. Briefly, we collected the following data from the Medical Image Bank of the Valencian Community from the Department of Universal Health and Public Health Service: sex and age at entry in the study, radiological examination, and date.…”
Section: Methodsmentioning
confidence: 99%